Ebeveynlerin Özel Gereksinimli Çocuklara Yönelik Algılarının İncelenmesi - Etgüer, Damla; Ünsever, Özge; TORAN, MEHMET (My University, 2017)
Amaç: Bu araştırmanın amacı normal gelişim gösteren çocuk ebeveynlerinin özel gereksinimli bireyler hakkındaki farkındalıkları, onları nasıl algıladıkları, çocuklarına özel gereksinimli bireyleri nasıl anlattıklarını incelemektir. Yöntem: Araştırmada yöntem olarak nitel araştırma yöntemi benimsenmiştir. Araştırmanın çalışma grubundan elde edilen verilerin analizinde bir durum saptaması ve görüşlerin incelenmesi yapıldığı için betimsel analiz tekniği kullanılmıştır. Çalışma grubunun oluşturulmasında kartopu örnekleme yöntemi kullanılmıştır. Araştırmanın çalışma grubunu; çocukları normal gelişim gösteren ve okul öncesi eğitim kurumuna devam eden 17 ebeveyn oluşturmaktadır. Ebeveynlerin tamamı etik olarak izin alınmış ve araştırmaya gönüllü katılmış anneler oluşturmaktadır. Araştırmanın veri yöntemi olarak görüşme yöntemi kullanılmıştır. Görüşmelerin gerçekleştirilmesi için araştırmacılar tarafından yarı yapılandırılmış görüşme formu oluşturularak ebeveynlerden derinlemesine görüşmeler yapılmıştır. Görüşmelerden sonra veriler dokümante edilerek betimsel analiz ilkeleri doğrultusunda kategoriler ve temalar oluşturulmuştur. Bulgular ve Sonuç: Araştırmanın bulguları incelendiğinde, ebeveynlerin özel gereksinimli bireylerin farkında oldukları, özel gereksinimli bireyleri normal gelişim gösteren çocukları ile aynı ortamda bulunmalarının önemine vurgu yaptıkları, kamusal alanın özel gereksinimli bireylerin ihtiyaçlarına göre düzenlemesine yönelik farkındalıklarının olduğu bulunmuştur.

Objectives: The purpose of this study is to examine the awareness and knowledge of parents with normally developed children regarding children with special needs; how they perceive and how they describe individuals with special needs to their children. Method: In this study, the qualitative research method was adopted. And the descriptive analysis method was employed because situation determination and opinions were examined in the analysis of the data obtained from the study group. Snowball sampling method was used to form and gather up the study group. 17 parents who have children with normal development and go on preschool education institution constituted the study group of the research. The parents were composed the mothers have given informed consent and voluntarily participated into the study. The interview method was used as the data method of the research. In order to conduct the interviews, researchers formed a semi-structured interview form and thus, it would be possible to conduct indepth interviews with the parents. After the interviews, the data was documented and categories and themes were formulated in the light of descriptive analysis principles. Result and Conclusion: When the findings of the study were examined, it was found out that parents have a genuine awareness concerning children with special needs in that they emphasize the importance of interaction between their children with normal development with the children with special needs by coming together in the same environment, and they also have an awareness regarding the need of the public spaces’ regulations according to the children with special needs.
Investigation of the Parents’ Perceptions towards Children with Special Needs
Keywords: Ebeveyn; ebeveyn tutumları; özel eğitim; özel gereksinimli bireyler; Parents; parental attitudes; special education; individuals with special needs